2022
DOI: 10.1007/s12325-022-02333-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Management of Bleeding Complications with Direct Oral Anticoagulants in Patients with Atrial Fibrillation and Venous Thromboembolism: a Narrative Review

Abstract: Atrial fibrillation (AF) and venous thromboembolism (VTE) are highly prevalent conditions with a significant healthcare burden, and represent the main indications for anticoagulation. Direct oral anticoagulants (DOACs) are the first choice treatment of AF/VTE, and have become the most prescribed class of anticoagulants globally, overtaking vitamin K antagonists (VKAs). Compared to VKAs, DOACs have a similar or better efficacy/safety profile, with reduced risk of intracerebral hemorrhage (ICH), while the risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 154 publications
1
34
0
Order By: Relevance
“…This may be due to increasing awareness of apixaban’s optimal efficacy/safety profile compared with other DOACs. 155 This pattern may not have been followed with edoxaban, although data on its uptake is sparse. None of the switching studies included in this review accounted for OAC dose.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to increasing awareness of apixaban’s optimal efficacy/safety profile compared with other DOACs. 155 This pattern may not have been followed with edoxaban, although data on its uptake is sparse. None of the switching studies included in this review accounted for OAC dose.…”
Section: Discussionmentioning
confidence: 99%
“…5 Real-world studies and national registries demonstrated that major bleeding-including intracranial hemorrhage (ICH) and gastrointestinal bleeding (GIB)-occurs in up to 6.62 DOAC users per 100 treatment years. 6,7 With the expanded use of DOACs in clinical practice, DOAC-associated major bleeding is expected to be encountered more frequently in the emergency department. The number of hospitalized patients in the United States due to DOAC-related bleeding grew from 90 000 in 2015 to nearly 190 000 in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…12 Therefore, prompt diagnosis and proper management of major bleeding are critical to reduce the mortality risk and short-and long-term morbidities. 6 Until recently, the management of major bleeding complications in DOAC users received little attention from international guidelines due to the lack of specific reversal agents. The introduction of reversal antidotes has significantly improved the outcomes of emergency bleeding among DOAC users.…”
Section: Introductionmentioning
confidence: 99%
“…However, their use entails significant drawbacks in the form of elevated bleeding risks, which can lead to severe complications. 10 Therefore, it is crucial to identify patients at risk and to expand our understanding of the pathophysiology to enable a more targeted prevention and treatment of DVT.…”
Section: Introductionmentioning
confidence: 99%